Strategi Pemasaran Korean Street Food Pada UMKM Di Pasar Cidu Makassar Untuk Meningkatkan Volume Penjualan Dengan Media Sosial Sebagai Variabel Intervening - Sri Utami; Hikmayani Subur (CV. ALIM'SPUBLISHING, 2024)
This research aims to investigate the effect of Korean Street Food marketing strategies on MSMEs in Pasar Cidu Makassar on increasing sales volume, with social media as an intervening variable. Quantitative methods were used in this research by collecting data through surveys of 50 MSME owners or managers at Pasar Cidu Makassar who actively use social media in their marketing strategies. The results of multiple regression analysis show that marketing strategy has a significant direct influence on social media (path coefficient = 0.541, p < 0.05) and sales volume (path coefficient = 0.646, p < 0.05). In addition, social media also has a significant influence on sales volume (path coefficient = 0.062, p < 0.05), acting as a mediator between marketing strategies and increasing sales volume. Path analysis shows that the total effect of marketing strategy on sales volume is 0.6795, which indicates the existence of significant direct and indirect effects. These findings emphasize the importance of integrating marketing strategies and social media in an effort to increase the sales volume of Korean Street Food MSMEs at Cidu Makassar Market.